Associations between adiposity, diabetes, lifestyle factors and the risk of gliomas - Liu, Xiaozhi; Wang, Yang; Wang, Yuxiang; Zhao, Jincheng; Shi, Wanchao; Zhao, Yujun; Chen, Lei; Wu, Lei (Frontiers in Medicine, 2023)
Background Despite numerous observational studies linking adiposity, diabetes, and lifestyle factors with gliomas, the causal associations between them remain uncertain. Methods This study aimed to use two-sample Mendelian randomization (MR) analysis to investigate whether these associations are causal. Specifically, independent genetic variants in body mass index (BMI), waist circumference (WC), type 2 diabetes (T2D), smoking, alcohol, and coffee consumption were extracted from the published genome-wide association studies (GWASs) with genome-wide significance. The corresponding summary-level data for gliomas were available from a GWAS of 1,856 cases and 4,955 controls of European descent from the GliomaScan consortium. Additionally, glioma pathogenesis-related protein 1 data were used for validation, and Radial MR analysis was conducted to examine the potential outlier single-nucleotide polymorphisms (SNPs). Results One standard deviation (SD) increase in BMI had an odds ratio (OR) of 1.392 (95% confidence interval (CI), 0.935–2.071) for gliomas, while one SD increase in WC had an OR of 0.967 (95% CI, 0.547–1.710). For T2D, a one-unit increase in log-transformed OR had an OR of 0.923 (95% CI, 0.754–1.129). The prevalence of smoking initiation had an OR of 1.703 (95% CI, 0.871–3.326) for gliomas, while the prevalence of alcohol intake frequency had an OR of 0.806 (95% CI, 0.361–1.083), and the prevalence of coffee intake had an OR of 0.268 (95% CI, 0.033–2.140) for gliomas. Conclusion This study provides evidence that adiposity, T2D, smoking, alcohol drinking, and coffee intake do not play causal roles in the development of gliomas. The findings highlight the importance of reconsidering causal relationships in epidemiological research to better understand the risk factors and prevention strategies for gliomas.